Pengaruh Sirih (Areca catechu) Sebagai Intelmentika Terhadap Nematode Gastrointesninal Pada Kambing - Yudha Fahrimal (Jurnal Agripet, 2002)
ABSTRACT.The efficacy and effective dose of bettlenut (Areca catechu) powder against gastrointestinal nematode worms was studied. Twenty five local goats at the age of 1 1.5 years of age weighing 8 to 12 kg were used in this study. All goat were naturally infected with gastrointestinal nematodes and they all had fecal egg count 3000/gram. The goats were randomly divided into 5 group: group I as a non treated control and group I, II, III, IV, and V were given bettlenut powder 5 gram, 10, 15 and 20 gram, respectively. The nematode worm were identified and grouped into family of Trichostrongylidae (Trichostrongylus sp. and Haemonchus sp.) and strongylidae (Bunostomum sp., Oesophagostomum sp. and Strongylus sp.). in general, bettlenut powder in all doses is very effective against gastrointestinal nematode worms from both families compare to control group (P 0.01) and no significant different among administered doses (P 0.05). Bettlenut powder in all doses given is vey effective (P 0.01) against Trichostrongylus sp. and Haemonchus sp. from family of Trichostrongylidae. Bettlenut powder in all doses given is also very effective (P 0.01) against Bunostomum sp., Oesophagustomum sp. and effective (P 0.05) against Strongylus sp. from family of Strongylidae. The dose of 5 gram of bettlenut powder per goat is recommended for treating goat invested with gastrointestinal nematode worms because it is saver and can be given more than once.